Harrison's rheumatology - Fauci, Anthony S. 1940-; Langford, Carol A.; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Medical, 2013)
Featuring a compilation of chapters on rheumatology that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Features: Current, thorough coverage of important immunology and rheumatology topics, including the immune system in health and disease, disorders of immune-mediated injury, and disorders of the joints and adjacent tissues. Delivers insights designed to reduce pain, lesson joint and organ damage, and improve overall patient outcomes. Integrates pathophysiology with clinical management. 75 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Content updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, 24 chapters written by physicians who are recognized experts in the field of rheumatology. Helpful appendix of laboratory values of clinical importance.